Enhancing wireless applications through reconfigurable electro-mechanical reflectarray antenna design for beam steering - Behrokh Beiranvand; Rashid Mirzavand (Scientific Reports)
Abstract The growing interest in reconfigurable intelligent surfaces (RIS) for wireless communications is evident, particularly in addressing challenges beyond the normal incidence condition of electromagnetic waves. This paper introduces an innovative approach to achieve beam steering in reflecting-type array structures, specifically reflectarrays, through the use of Reconfigurable Electro-Mechanical Reflectarray (REMR) technology. The REMR structure, equipped with a cam-shaped actuator beneath each unit cell’s ground plane, serves as the basis for this design. The proposed design involves multiple reflective strips at variable heights, enabling significant adaptability to incident waves at various angles. By incorporating a cam-shaped actuator beneath the ground plane of each unit cell, a mechanical phase shifter acts as a continuous modifier of phase for incident waves, resulting in the realization of the REMR effect. The REMR structure demonstrates consistent phase and amplitude responses, facilitating efficient beam steering. Simulation and measurement results show a remarkable unwrapped phase shift range of $$\sim 200^° $$ and beam steering over a broad spectrum of incidence angles from $$0^° $$ to $$70^° $$ . Additionally, the REMR structure maintains stability even when powered off in the “defined gradient mode” due to a memory function preserving gradient states. The fabrication process utilizes 3D printers, offering flexibility and ease of customization. This comprehensive approach holds significant potential for advancing RIS technologies.